HUBUNGAN USIA DAN PENDIDIKAN DENGAN PENGETAHUAN IBU TENTANG STUNTING PADA BALITA - Heryanti - Heryanti (Masker Medika, 2023)
Introduction: The failure to reach growth and development potentials (stunting) is a cumulative effect of nutrient problems.Base on WHO in 2020, the number of stu ting increased to be 149.2 million children (22%) compared to 2019 which was 144 children ( 21,3%). This research aims to find out the relation of age and education with women’s knowledge about Stunting to under five years old children at BPM Hj. Zuniawaty Palembang in 2022. Method: This research used analytic survey method. The populasion for this research was all women visited BPH Hj. Zuniawaty Palembang by taking their children from October to December 2022. The sampel taken for this research was accidentally sampling who where only 41 respondents. Result: By the result of Univariate showed 36 respondents (87.8%) had good knowledge meanwhile 5 respondent (12.2%) had low knowledge. Woman with early adult years were 28 respondent (68.3%) more than the woman with late adult years were 13 respondent (31.7%). Women with high education level were 30 respondent (73.2%) more than women with low education level were 11 respondent (26.8%). Discussion: Bassed on this statistical result, it means there was a relation between age education and women’s knowledge about Stunting to under five year old children